2015
DOI: 10.1109/tsipn.2015.2477777
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Voting/Ranking With Optimal Number of States per Node

Abstract: Considering a network with n nodes, where each node initially votes for one (or more) choices out of K possible choices, we present a Distributed Multi-choice Voting/Ranking (DMVR) algorithm to determine either the choice with maximum vote (the voting problem) or to rank all the choices in terms of their acquired votes (the ranking problem). The algorithm consolidates node votes across the network by updating the states of interacting nodes using two key operations; the union and the intersection. The proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…The Plurality Problem (also known as Plurality Consensus Problem in Distributed Computing), is an extensively studied problem in many areas of distributed computing, such as population protocols [1,8,9,21,24], fixed-volume Chemical Reaction Networks [13,27], asynchronous Gossip protocols [5,6,10,15,16], Statistical Physics [12] and Mathematical Biology [7,11,20,26].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…The Plurality Problem (also known as Plurality Consensus Problem in Distributed Computing), is an extensively studied problem in many areas of distributed computing, such as population protocols [1,8,9,21,24], fixed-volume Chemical Reaction Networks [13,27], asynchronous Gossip protocols [5,6,10,15,16], Statistical Physics [12] and Mathematical Biology [7,11,20,26].…”
Section: Related Workmentioning
confidence: 99%
“…In the context of the Plurality Problem, for k = 2, the protocols of [9,21] require 4 states per node, and in [21], they showed that the problem cannot be solved with 3 states. For general k, the protocol of [24] uses O(2 k−1 · k) states per node, and the only lower bound known has been so far the trivial Ω(k), as each node/agent needs at least k distinct states to specify its own opinion (which is from a set of size k). Under the crucial assumption that agents initially agree on a representation of the input values as distinct integers, [17] provides an elegant solution to the Plurality Problem which employs O(k 6 ) states only.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the algorithm termination is embedded within it. Hence, the algorithm becomes more efficient in terms of message complexity compared with previous works [7,10]. We call this algorithm 'binary voting with SPRT' (BiSPRT) algorithm.…”
Section: Introductionmentioning
confidence: 99%